TAHAP-TAHAP PENGADAAN TANAH UNTUK PEMBANGUNAN UTILITAS KERETA CEPAT JAKARTA-BANDUNG - Glorya Kalicya; Gunawan Djajaputra (Jurnal Hukum Adigama, 2020)
"Land acquisition is an activity of providing land by giving appropriate and fair compensation to the right parties.", this is stated in Article 1 paragraph 2 of Law Number 2 of 2012 concerning Land Procurement for Development in the Public Interest. At present, the Government of Indonesia is working on development for infrastructure needs, one of which is the Kereta Cepat Jakarta Bandung (KCJB), Utility Development by PT. Kereta Cepat Indonesia China (KCIC) located in the Jakarta to Bandung area. Therefore, the Government held a Land Procurement in the Jakarta to Bandung area so that the Kereta Cepat Jakarta Bandung, Utility Development can meet the interests of the community. In the implementation of land acquisition, there are things that become obstacles for the implementation of KCJB Utilities Development. For this reason, Law No. 2 of 2012 is present to provide hope that the Agency which conducts land acquisition can resolve conflicts carried out during its implementation. The purpose of this research is to study land acquisition for KCJB Utilities Development which is reviewed based on Law Number 2 of 2012 concerning Land Procurement for Development in the Public Interest.